2008
DOI: 10.1007/s00223-008-9191-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism: Role of the Preoperative Oral Calcium Loading Test in the Differential Diagnosis Between Adenoma and Hyperplasia

Abstract: Whereas the sensitivity of the membrane calcium receptors is decreased in parathyroid adenoma, extracellular calcium may reduce parathyroid hormone (PTH) secretion through the protein kinase C pathway in parathyroid hyperplasia. The aim of this study was to determine the role of a preoperative oral calcium loading test in the differential diagnosis between adenoma and hyperplasia. Twenty-two subjects with adenoma (group A, age +/- standard error 56 +/-2 years, female/male 15/7), 10 individuals with hyperplasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…PTH decline >60 % diagnosed hyperplasia with specificity of 100 %. The total accuracy of the test was 65 % [ 66 ]. This model has not been confirmed by other groups.…”
Section: Preoperative Diagnosis Of Sporadic Multiglandular Diseasementioning
confidence: 99%
“…PTH decline >60 % diagnosed hyperplasia with specificity of 100 %. The total accuracy of the test was 65 % [ 66 ]. This model has not been confirmed by other groups.…”
Section: Preoperative Diagnosis Of Sporadic Multiglandular Diseasementioning
confidence: 99%
“…Robert et all suggested that PTH level <4 times the upper limit of normal excludes malignancy [19]. Case series studying solitary parathyroid adenomas with asymptomatic disease derived mean preoperative PTH levels of 186 pg/mL [20] and 165 pg/mL [21], while research studying parathyroid carcinoma yielded higher PTH levels of 714 pg/mL [22] and 1220 pg/mL [23]. The huge size of the cystic adenoma (11 x 7 x 6 cm) in our case is extremely rare [3], though giant parathyroid cysts of up to 15 cm in diameter have also been reported [24].…”
Section: Discussionmentioning
confidence: 99%
“…To further stress the benefit of PTH in preoperative diagnosis, Robert et al suggested that a PTH level <4 times the upper limit of normal excludes a malignancy [4]. Other studies support the above trend—a recent case series looking at solitary adenomas causing asymptomatic disease have derived mean values of Preoperative PTH as 186 [5] and 165 ng/L [6], while research into carcinoma show higher PTH levels of 714 [2] and 1220 ng/L [7]. This consolidates the unusual nature of a PTH level of 3957 ng/L in an adenoma with no radiological, Intraoperative, or histological evidence of malignancy.…”
Section: Discussionmentioning
confidence: 99%